Penerapan Kekayaan Media Berdasarkan Pemaknaan Analisis Konten Flayer Dakwah pada Instagram MTA TV Periode 2021 - 2025 - Alfian Arif Wibowo; Rahmat Wisudawanto; Dyah Retno Pratiwi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study discusses how the application of media wealth by MTA TV's public relations in delivering da’wah messages through Instagram flyers on @mtatv_official in the period of 2021-2025. The research employed a descriptive qualitative approach with Roland Barthes' semiotic analysis, focusing on denotation, connotation, and myths. The findings reveal that MTA TV has effectively implemented four key elements of media wealth—signal diversity, language variations, personal sources, and regardless—through its use of Instagram flyers. These elements are designed to enhance the communication process, making the messages more engaging and accessible to the audience. The da’wah messages conveyed through the flyers are interpreted by the audience in three primary categories: invitation (76.67%), motivation (16.67%), and solidarity (6.67%). The majority of the audience interprets the messages as invitations to join or engage in religious activities, highlighting the importance of outreach and engagement in MTA TV's approach. The motivational aspect encourages positive actions and attitudes towards religious teachings, while solidarity, though less prevalent, emphasizes the sense of community and support within the Muslim audience. The use of media wealth on social media platforms like Instagram is shown to increase the effectiveness of da’wah messages by making them more visually appealing, interactive, and relatable to a wide audience. This study suggests that employing rich media content, such as Instagram flyers, can play a vital role in enhancing the reach and impact of religious communication. It also underscores the importance of understanding the semiotic elements in shaping how messages are interpreted by different segments of the audience, making it a valuable tool for religious organizations aiming to modernize their communication strategies.